Enhancing the photocatalytic hydrogen production of the ZnO–TiO2 heterojunction by supporting nanoscale Au islands. (6th October 2021) - Ramírez-Ortega, David; Guerrero-Araque, Diana; Acevedo-Peña, Prospero; Reguera, Edilso; Calderon, Hector A.; Zanella, Rodolfo
Abstract: In this work, Au was loaded on the ZnO–TiO2 heterojunction by the deposition-precipitation with urea method to boost its photocatalytic hydrogen production. The synthesized materials were characterized by TEM, ICP-OES, XRD, N2 adsorption-desorption, UV–vis spectrophotometry, XPS, and (photo)electrochemical measurements. The TEM images confirmed the close contact between ZnO and TiO2 nanoparticles and showed that although Au nanoparticles agglomerated in the form of islands; they were widely dispersed on the surface of the photocatalysts. Besides, the XPS characterization revealed the enhanced contribution by the metallic Au species as their amount was increased in the composite. The heterojunctions with different Au contents produced higher yield in the photocatalytic production of hydrogen, observing a maximum with the 2-wt.%- Au content (9.13 mmol g −1 ), being this value 6 times higher than the results obtained with the ZnO–TiO2 heterojunction. This improvement is associated with the synergistic interaction between the ZnO–TiO2 heterojunction and Au islands that promoted the separation and transfer of charge carriers. Besides, the (photo)electrochemical characterization showed that the islands acted as "electronic reservoirs", prolonging the lifetime of the photogenerated electron-hole pairs and creating surface or energy states at the Au/ZnO–TiO2 heterojunction interface. These states helped improve the charge transfer processes by diminishing the recombination and increasing the photocatalytic hydrogen production. Graphical abstract: Image 1 Highlights: Au nano islands were formed onto ZnO–TiO2 by deposition-precipitation with urea. Characterization of Au/ZnO–TiO2 evidenced the formation of heterojunctions. XPS evidenced the enhanced contribution of metallic Au species. Hydrogen generation increase up to 6 times by using Au nano islands co-catalyst. Au islands acted as "electronic reservoirs" increasing the hydrogen generation.